Legal Effectiveness of E-Purchasing Implementation in Government Procurement: An Empirical Study from fhe Perspective of Transparency and Fairness in Indonesia - Narendra Tricahya Pratama; Winsherly Tan; Nurlaily Nurlaily (JUSTISI, 2026)
This study aims to analyze the effectiveness of e-purchasing implementation in the government sector from the perspectives of transparency and fairness. The method used in this study is empirical approach with data collected through interviews, observation, documentation, and literature review. Data were analyzed qualitatively using a descriptive-analytical method based on Soerjono Soekanto’s theory of legal effectiveness. The research was conducted in Indonesian government agencies, involving Commitment-Making Officials (PPK) and Budget-Using Officials (KPA) as informants. The novelty of this research lies in the gap between the ideal (das sollen) and reality (das sein) in the implementation of e-purchasing, where, normatively, this system is designed to ensure transparency and accountability; however, in practice, deviations as well as structural and cultural barriers within the procurement bureaucracy are still observed. The results of the study show that although regulations governing the procurement of goods and services are sufficiently robust, the implementation of e-purchasing still faces various challenges, such as technical system barriers, resistance from procurement officials, infrastructure limitations, and a bureaucratic culture that does not yet fully support the principle of transparency. Additionally, indications of fictitious procurement practices were found, suggesting weak oversight and enforcement of the law. Conclusion of this study is that the effectiveness of e-purchasing implementation has not yet been fully achieved. Therefore, it is necessary to strengthen technical regulations, improve human resource capacity and infrastructure, foster a bureaucratic culture that is transparent and accountable, and implement stricter and more systematic oversight to ensure that e-purchasing truly becomes an instrument of procurement modernization oriented toward the public interest.